Isolation, Identification and Characterization of Yeasts from Fermented Goat Milk of the Yaghnob Valley in Tajikistan - Qvirist, Linnea A.; De Filippo, Carlotta; Strati, Francesco; Stefanini, Irene; Sordo, Maddalena; Andlid, Thomas; Felis, Giovanna E.; Mattarelli, Paola; Cavalieri, Duccio (Frontiers in Microbiology, 2016)
The geographically isolated region of the Yaghnob Valley, Tajikistan, has allowed its inhabitants to maintain a unique culture and lifestyle. Their fermented goat milk constitutes one of the staple foods for the Yaghnob population, and is produced by backslopping, i.e., using the previous fermentation batch to inoculate the new one. This study addresses the yeast composition of the fermented milk, assessing genotypic, and phenotypic properties. The 52 isolates included in this study revealed small species diversity, belonging to Kluyveromyces marxianus, Pichia fermentans, Saccharomyces cerevisiae, and one Kazachstania unispora. The K. marxianus strains showed two different genotypes, one of which never described previously. The two genetically different groups also differed significantly in several phenotypic characteristics, such as tolerance toward high temperatures, low pH, and presence of acid. Microsatellite analysis of the S. cerevisiae strains from this study, compared to 350 previously described strains, attributed the Yaghnobi S. cerevisiae to two different ancestry origins, both distinct from the wine and beer strains, and similar to strains isolated from human and insects feces, suggesting a peculiar origin of these strains, and the existence of a gut reservoir for S. cerevisiae. Our work constitutes a foundation for strain selection for future applications as starter cultures in food fermentations. This work is the first ever on yeast diversity from fermented milk of the previously unexplored area of the Yaghnob Valley.